Analysis of Heti Lapang Tradition in Nangatobong Village, Sikka Regency - Ivon, Fransiska Nona; Yanto, Yanto; Nasa, Rikardus (The Indonesian Institute of Science and Technology Research, 2024)
Every village must have different traditions, cultures, customs or habits. These traditions are also local wealth owned by the nation, always to be maintained, preserved, and guarded so that these traditions do not become extinct. Heti Lapang is a tradition of getting rid of bad luck which is done after someone experiences bad things such as accidents or nightmares. Heti Lapang tradition is an important part of the Nangatobong community. This study aims to describe the process of the Heti Lapang tradition and find out the meaning contained in the process of the Heti Lapang tradition. The results indicate that the process of Heti Lapang has four processes, namely, roni keleng means getting rid of bad things in a person who experiences a disaster, pati tali means opening the way, huler wair means sprinkled with coconut water so that it can provide coolness and to free people from evil and the last is tung goit which means delivering bad things in the form of symbols or objects used during the Heti Lapang process. In each implementation, verses are spoken using traditional language by mentioning the name of the person who suffered a disaster or accident. The meaning contained in the process of the Heti Lapang Tradition ceremony is to bring safety to the community so that the same disaster does not happen again.